Simulation of the aircraft parachuting process to the runway during landing - Liudmyla Kapitanova; Viktor Riabkov; Danylo Kirnoson (Авіаційно-космічна техніка та технологія, 2024)
The landing of an aircraft is an unknown part of its flight, and at this stage, the highest number of accidents and even disasters are observed. It should be noted that the movement of the aircraft in its airspace, when it is under the influence of aerodynamic forces, gravity, and engine thrust, is quite accurately modeled by various authors and presented in printed sources. The peculiarities of the aircraft’s movement during air-to-ground landing, i.e., at the moment of parachuting directly onto the runway, are insufficiently studied. The influence of parachuting conditions on post-landing stability has barely been studied. The subject of study in this article is the modeling of the parachuting process under conditions of aircraft landing. The goal of this study is to develop and test mathematical and simulation models of the aircraft’s movement during its parachuting from the alignment zone to the runway and to ensure the stability of longitudinal movement at the moment of the first landing impact and subsequent movement. Tasks: analyze the characteristics of the landing distances of transport category aircraft; establish the features of the parasailing stage of the aircraft during landing; develop a parametric model of the aircraft in its parachute configuration; establish conditions for modeling shock-absorbing landing gear; and, based on general and simulation models, establish zones of longitudinal movement stability of the aircraft after the first landing. Based on the results of experimental studies, the proposed mathematical model of the aircraft in landing configuration and the simulation model of participation in the landing of shock-absorbing landing gear systems quite reliably (compared to experimental data) estimate the aircraft’s movement at the moment of its touchdown and subsequent roll. This means that mathematical modeling can avoid repeated bounces during landing, ensure stability of longitudinal aircraft movement, reduce the length of the unbraked roll, and decrease the required runway length during aircraft landing. Conclusions: By analyzing normalized landings, the six most characteristic stages in the landing distance of transport category aircraft have been identified. A method of mathematical modeling of aircraft movement during parachuting onto the runway, considering not only the glider’s characteristics but also the features of the landing gear shock-absorbing systems, allows evaluating the parameters of parachuting that ensure stability of longitudinal aircraft movement after the first impact on the landing gear. Using the example of the An-140 aircraft, it is demonstrated how the values of brake wheel stability parameters are ensured and how the parachuting speed affects the length of its landing distance.